Scaffolding geology content and spatial skills with playdough modeling in the field and classroom. Issue 1 (2nd January 2023) - Bateman, Kathryn M.; Ham, Joy; Barshi, Naomi; Tikoff, Basil; Shipley, Thomas F.
Abstract: Spatial skills are embedded in all aspects of the geosciences. The teaching and learning of spatial skills has been a challenging, but vital, endeavor. To support student learning of spatial skills in undergraduate courses, we designed scaffolds for spatially dependent content in a mid-level geoscience course using playdough to allow students to model and manipulate geologic structures and processes. Using a semester-long geology course as a case study, we explore the ways in which students reported playdough supported their learning of geoscience content during the course. Students found the playdough most helpful for visualizing geologic structures, such as faults and domes, which students were then able to encode into their long-term memories, or "mental libraries, " for application to new contexts on assessments later. The playdough was more helpful at the start of the course when students were grappling with introductory course content and skills. Later in the course, the need for the playdough as a scaffold faded, as intended. Most students eventually sought new scaffolds, such as three-dimensional block models, which illustrate more complex and sophisticated structures and processes. Therefore, we see playdough as a useful scaffold for students in the early stages of spatial and geologic skill development as it aids students in developing both sets of skills. It is easy to utilize, inexpensive, portable, widely available, and familiar to most students.